(untitled) (International Journal of Engineering and Computer Science, 2017)
In rapid growth of internet, the amount of web information gathering becomes a challenging point for all users. Many existing retrieval systems have been developed to attempt to satisfy this problem. But still there is no complete solution to the problem. Ontology describes and formalizes standardized representation of knowledge as a set of concepts and the relationship between those concepts. In personalized web information gathering ontology is also used to represent the user profiles. For representing user profiles many existing models have been provided knowledge from either global or local knowledge base. The user background knowledge can be better discovered if we integrate global and local analysis. The proposed system emphasizes the specific semantic relation in one computational model. Ontology contains lots of instances. Automatically instance matching has become the fundamental issue. Instance matching approach is used to present based on discriminative property value. Ontology model in domain specific system with instance search gives more accurate result.